PEMBINAAN KESADARAN BERAGAMA SEBAGAI UPAYA PENINGKATAN PEMAHAMAN AGAMA ISLAM DI LAPAS KELAS IIB ANAK WANITA TANGERANG - Totong Heri (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Correctional institutions are a place of guidance for people who are ensnared by the law. In connection with this coaching, this study tries to describe the activities of Islamic Religious Education held in the Class IIB Lapas for Tangerang female children in an effort to improve religious understanding with the direct observation method. The results of the study that Islamic religious education activities in Lapas class IIB Tangerang female children run well and positively. It was concluded that efforts to increase understanding of Islam were carried out using several methods that were no different from the method of guidance in general. Among them such as the lecture method, the method of learning the Koran, as well as the muhasabah and dhikr methods. The obstacles that occur in Islamic religious education activities are the lack of awareness of prisoners in carrying out the process of religious activities and the lack of attention from the Government in the provision of teaching staff and infrastructure in the implementation of religious activities.